1995
DOI: 10.1002/ajmg.1320600105
|View full text |Cite
|
Sign up to set email alerts
|

Autism, affective disorders, and social phobia

Abstract: The purpose of this study is to test the hypothesis that major affective and/or anxiety disorders are increased among relatives of autistic probands compared with controls. Among 36 families with an autistic child, 23 (64%) have a first degree relative diagnosed with major depressive disorder and 14 (39%) have a first degree relative diagnosed with social phobia. These rates are significantly greater than the 19% and 5%, respectively, found among 21 families with a child having a genetic condition, tuberous sc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

12
138
1
3

Year Published

1996
1996
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 184 publications
(154 citation statements)
references
References 32 publications
12
138
1
3
Order By: Relevance
“…However, there is also evidence that children with autism and severe mental retardation have higher levels of anxiety than children of similar cognitive functioning without autism (Bradley et al 2004). The observation that both symptoms of simple phobia and social phobia were equally common in higher and lower IQ subjects is intriguing, and might be hypothesized to show that these specific forms of anxiety fall closer to the core phenotype of the PDDs as opposed to representing comorbidities, as also suggested by family studies (Smalley et al 1995). Our data also showed that in children with IQ below 70, the correlations of anxiety with hyperactivity and inappropriate speech were significantly stronger than in children with IQ above 70.…”
Section: Discussionmentioning
confidence: 91%
“…However, there is also evidence that children with autism and severe mental retardation have higher levels of anxiety than children of similar cognitive functioning without autism (Bradley et al 2004). The observation that both symptoms of simple phobia and social phobia were equally common in higher and lower IQ subjects is intriguing, and might be hypothesized to show that these specific forms of anxiety fall closer to the core phenotype of the PDDs as opposed to representing comorbidities, as also suggested by family studies (Smalley et al 1995). Our data also showed that in children with IQ below 70, the correlations of anxiety with hyperactivity and inappropriate speech were significantly stronger than in children with IQ above 70.…”
Section: Discussionmentioning
confidence: 91%
“…This hypothesis is strengthened by finding a sizable homogeneous group of children with autism who have a family history of major affective disorder, have symptoms of affective disorder themselves, and respond to a SSRI used also to treat major affective disorders. A high incidence of major affective disorders has been observed repeatedly in the family histories of children with autism in comparison with control groups and/or population rates (DeLong and Dwyer 1988, Piven et al 1990, Smalley et al 1995, Bolton et al 1998). However, there has been scant attention given to the similarities of autistic symptomatology and that of affective disorders.…”
Section: Discussionmentioning
confidence: 99%
“…Others have implied that autism in some forms may represent a variant in the genetic expression of depression (Cook et al 1994, Smalley et al 1995. Ghaziuddin and Greden (1998) consider depression to be a distinct, presumably incidental, condition in some children with autism/pervasive developmental disorder, but they have not related this to the incidence of major affective disorder in the families nor to the etiology of autism.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…18,19 Therefore, given its role in anxiety, the GABAA receptor might be considered a candidate gene for autism. The GABAA receptor also appears to play a role in several behaviors associated with autism; mice with a targeted deletion of the murine garb3 gene are hyper-responsive to human contact, fail to nurture offspring, are hyperactive, often run in tight circles, and have occasional epilepsy.…”
Section: Molecular Psychiatrymentioning
confidence: 99%